KOMPARASI PENGGUNAAN BAHASA JURNALISTIK ANTARARIAU.COM DAN RIAU24.COM PADA BERITA COVID-19 - Perrmana, Rico; ', Ismandianto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Online media that contains journalistic works in Riau, especially Pekanbaru, also reported developments, policies, and ways to handle Corona Virus Disease 2019 (Covid-19) since the spread of this disease in Indonesia. Journalistic language as the main thing in making news which must pay attention to applicable rules and important parts in the use of various journalistic languages and look for any deviations contained in writing journalistic works. The type of research used in this study is descriptive qualitative research using data collection techniques through observation, interviews, and documentation. Data were analyzed using the model of Miles and Huberman (1984) namely data collection, data presentation, data reduction and finally data verification. The results obtained by the research in distinguishing the use of jurnilstic language between Riau and Riau24 are found in the use of the Journalistic Code of Ethics (KEJ). The results of the study stated that between Riau and Riau24 there are some differences in the style of the journalistic language. Comparison of journalistic language deviations in Antara Riau as a news agency under the auspices of the government has many journalistic language deviations than Riau24 asaprivate news agency. The causes of this deviation include the use of Auto Correct on tools used such as Smartphones, Laptops, or Computers in the Editor's section. Another cause is not focused and lack of accuracy in writing and editing news. Human Error in these two media is still often an important factor in the deviations found in the news Keywords : Comparasion, Media, Journalistic, Covid – 19